Fixed-prize tournaments versus first-price auctions in innovation contests - Anja Schöttner (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2005)
This paper analyzes a procurement setting with two identical firms and stochastic innovations. In contrast to the previous literature, I show that a procurer who cannot charge entry fees may prefer a fixed-prize tournament to a first-price auction since holding an auction may leave higher rents to firms when the innovation technology is subject to large random factors.
Keywords: D44; H57; L15; 330; innovation contest; auction; tournament; quality